The primary role of sebum in the pathophysiology of acne vulgaris and its therapeutic relevance in acne management - James Q. Del Rosso; Leon Kircik (Taylor & Francis Group, 2024)
AbstractBackground Sebum physiology and its contributions to acne vulgaris (AV) pathophysiology have been long debated. Within the pilosebaceous unit, androgens drive sebocyte production of sebum, comprising mono-, di-, and triglycerides (the latter converted to fatty acids); squalene; cholesterol; cholesterol esters; and wax esters. Upon release to the skin surface, human sebum has important roles in epidermal water retention, antimicrobial defenses, and innate immune responses.Aims Alterations in sebum alone and with other pathogenic factors (inflammation, follicular hyperkeratinization, and Cutibacterium acnes [C. acnes] proliferation) contribute to AV pathophysiology. Androgen-driven sebum production, mandatory for AV development, propagates C. acnes proliferation and upregulates inflammatory and comedogenic cascades.Results Some sebum lipids have comedogenic effects in isolation, and sebum content alterations (including elevations in specific fatty acids) contribute to AV pathogenesis. Regional differences in facial sebum production, coupled with patient characteristics (including sex and age), help exemplify this link between sebum alterations and AV lesion formation.Conclusions To date, only combined oral contraceptives and oral spironolactone (both limited to female patients), oral isotretinoin and topical clascoterone (cortexolone 17α-propionate) modulate sebum production in patients with AV. A better understanding of mechanisms underlying sebaceous gland changes driving AV development is needed to expand the AV treatment armamentarium.